On the Total Irregularity Strength of the Corona Product of a Path with Path - Meilin Tilukay (Department of Mathematics, Faculty of Mathematics and Natural Sciences, Pattimura University, Ambon, Indonesia, 2023)
This paper deals with the totally irregular total labeling of the corona product of a path with path, cycle, and star. The results gave the exact values of the total irregularity strength of pm Pn and for integer 2 ≤ m ≤ 3 and n≥ 3